Effects of leaf ages, altitude and clone types on nutrient elements and antioxidant activity of tea (Camellia sinensis L. (O) Kuntze) in tropical conditions - Murdiono, Wisnu Eko; Salman, Nur Amirah Syafiqah; Ab Razak, Nor Asma; Halmi, Mohd Izuan Effendy; Wan, Jean Hong Yong; Mhd. Jalil, Abbe Maleyki; Burslem, David F.R.P.; Mahmud, Khairil (Elsevier B.V., 2025)
Tea is a globally popular heritage beverage consumed by over three billion people. The unique taste and health benefits of tea are linked to its nutrient composition and antioxidant activity (AOA). As a plant species, tea's nutrient elements and AOA vary based on season, altitude, clone type and leaf age. This study examined the nutrient composition and AOA of young and mature tea leaves from four clones (BC1248, TRI2024, AT53 and TV9) grown at different altitudes under tropical conditions in Malaysia. The results demonstrated that altitude and clone type significantly influenced (p < 0.05) foliar nutrient elements and AOA. Young tea leaves have higher nutrient levels and AOA than mature leaves across all clones. Interestingly, the foliar nutrient availability was higher in the highlands, although the variation across the four clones was insignificant (p > 0.05). On the other hand, foliar nutrient elements varied significantly among lowland tea clones, except for N and Ca. The highest AOA was recorded in young tea leaves of clone BC1248 at the lowland plantations, with total polyphenol contents (TPC), 2,2-diphenyl-1-picrylhydrazylradical (DPPH IC50), and ferric reducing antioxidant power (FRAP) values of 19.60 ± 0.15 mg GAE/g, 50.70 ± 1.86 µg/mL, 2.10 ± 0.14 mM Fe (II)/g, respectively. The DPPH IC50 and FRAP varied significantly (p < 0.05), except for TPC among the lowland and highland clones. Based on principal component analysis (PCA), we identified that the tropical lowlands of Malaysia were more suitable for growing tea with high AOA. These findings provide valuable insights for growers to develop sustainable tea farming strategies, ensuring optimal yield and targeted quality under tropical conditions.